Efektifitas Pengujian Kualitas Minyak Goreng Berdasarkan Indeks Bias: The Effectiveness of Testing the Quality of Cooking Oil Based on the Refractive Index - Rejeki, Herlina Putri Rejeki; Hasna Adiba; Bayu Setiaji (JFT : Jurnal Fisika dan Terapannya, 2023)
The refractive index of a solution is a very important characteristic parameter and several related parameters such as temperature, concentration, etc., can be estimated from it. The index of refraction of a substance is a measure of the speed of light in liquid compared to when in air. Refractive index is one of the parameters used to determine the quality of cooking oil. This study aims to determine the value of the refractive index of packaged cooking oil and bulk cooking oil, to compare the quality of packaged cooking oil and bulk cooking oil with the parameter of refractive index and to determine the effectiveness of testing the quality of cooking oil using the refractive index. The method used in this research is the experimental method, namely the refraction method using a parallel plan. From the experiment, it was found that the refractive index of packaged cooking oil is greater than that of bulk cooking oil. The refractive index of packaged cooking oil is 1,483 ± 0,044; while in bulk cooking oil 1,379 ± 0,024. This shows that the quality of packaged cooking oil is better than the quality of bulk cooking oil. The results obtained show that the use of the refractive index as a measure of the quality of cooking oil is considered effective. Keywords: Bulk Oil, Effectiveness, Packaged Oil, Quality, Refractive Index.